Serving Together Towards a Healthy Community to Implement Free Health in Bambe Village, Driyorejo District, Gresik Regency - Fasya, Abdul Hakim Zakkiy; Suherman, Alvianita; Yuliawati, Yuliawati (Journal of Health Community Service, 2023)
With increasing age, health problems are certainly more common in the elderly, this is due to the decline in the human immune system. Health problems that are often experienced are hypertension, cholesterol, blood sugar, uric acid and so on. The purpose of this activity is to carry out public health checks, especially the elderly. The total number of participants on the first day and the second day was 130 people. Documentation of the results of women's blood pressure checks 26 people in men 8 people, blood glucose when in women 8people in men 2 people. At this stage, the local midwife performs anamnesis and examinations, giving free medicine.